1991
DOI: 10.1126/science.252.5002.96
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Fermi Surface Nesting and Charge Density Wave Instability in Low-Dimensional Metals

Abstract: The concept of hidden Fermi surface nesting was introduced to explain the general observation that certain low-dimensional metals with several partially filled bands exhibit charge density wave (CDW) instabilities, although their individual Fermi surfaces do not reveal the observed nesting vectors. This concept was explored by considering the Fermi surfaces of the purple bronze AMo(6)O(17) (A = sodium or potassium) and then observing the CDW spatial fluctuations expected from its hidden nesting on the basis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
179
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(187 citation statements)
references
References 19 publications
8
179
0
Order By: Relevance
“…6a) with the stripe periodicity provides strong evidence that this is a CDW gap associated with the depletion of states around the Fermi level. The near-perfect inversion of contrast with bias polarity seen in Figure 4 is also characteristic of a true CDW 34 . The large gap size indicates a significant modification of the FS, but is consistent with that seen in other lamellar materials.…”
Section: Discussionmentioning
confidence: 69%
“…6a) with the stripe periodicity provides strong evidence that this is a CDW gap associated with the depletion of states around the Fermi level. The near-perfect inversion of contrast with bias polarity seen in Figure 4 is also characteristic of a true CDW 34 . The large gap size indicates a significant modification of the FS, but is consistent with that seen in other lamellar materials.…”
Section: Discussionmentioning
confidence: 69%
“…The extent of pockets should be limited in (q x ,q y ) plane in order to moderate blurring of the nesting construction; it should be also limited in q z direction, otherwise I-centering of the resulting pattern would be suppressed and disappear completely if a pocket transforms to a thin tube. In fact, even so-called "hidden" nesting [28], without a formation of real pocket, may be sufficient. We conclude with a note on a bulk character of all our observations.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the nesting character of the FS preserves, thus reflecting the incipient instability overcome by Coulomb scatterers. Nevertheless, to be sincere, it should be indicated that nesting is only a necessary condition (the so-called "hidden nesting" [279] may be considered as a property closely resembling the true nesting) of the CDW ordering to take place rather than the sufficient one. Certain relevant speculations describing opposite views can be found in References [280][281][282].…”
Section: Discussionmentioning
confidence: 99%